Integration of 2D Black Phosphorus Phototransistor and Silicon Photonics Waveguide System Towards Mid-Infrared On-Chip Sensing Applications - HUANG LI (Institute of Electrical and Electronics Engineers Inc., 2020)
10.1109/VLSIT.2018.8510658